ZORA 153: Slovenščina v Torontu in okolici nekoč in danes - Kralj, Tadej (University of Maribor Press, 2023)
ZORA 153: Slovenian Language in the Greater area of Toronto in the Past and Present. In the monograph I adress Slovene language as a heritage language in Slovene community of Toronto. The speakers who immigrated to another country maintained their language in their family environment and in organized Slovene community despite strong integration. They endured Slovene language to their descendants. The second generation that has grown up in Canada was in a contact with Slovene language and its cultural life until entering school. After entering it the communication in Slovene language was gradually replaced by communication in English. Even quicker integration in a wider social community and disappearance of Slovene language usage can be seen with the third or the fourth generation of immigrants’ descendants. I wanted to know if and how the representatives of different generations (the first, the second, the third and the fourth) strive to preserve Slovene language: with which purposes, how often they use it and with who, when and in which circumstances they communicate in Slovene language. I found out that in a selected environment the representatives of the first two generations preserve Slovene language with everyday communication (practical use of language) and also on cultural events (symbolic use of language). The use of Slovene language among representatives of the third and the fourth generation is disappearing even though the Canadian politics of multiculturalism encourages the use of heritage languages.